Lifestyle Behaviors Predict Adolescents Bullying Victimization in Low and Middle-Income Countries - Garcia-Hermoso, A (Elsevier B.V., 2020)
Background: In this study we aimed to provide a global perspective of the association between different lifestyle behaviors and bullying in school adolescents and to ascertain whether or not the Human Development Index moderated those associations. Methods: Data from the Global school-based Student Health Survey were analyzed in 273 121 from 82 countries. Logistic regression was applied to determine country-specific bullying victimization probability from meeting the recommended guidelines for physical activity, excessive sitting time, physical education attendance and active transport. Meta-analysis was then undertaken to ascertain pooled global effect estimates of the relationship between these behaviors and bullying victimization. Linear regression was used to study the relationship between odds of bullying from meeting the lifestyle guidelines and the Human Development Index. Results: Our estimates indicate that excessive sitting time [1.38 (1.34,1.41)], attendance to physical education [0.87 (0.85,0.89)], and active transport [0.94 (0.91,0.97)] but not overall physical activity [1.01 (0.99,1.04)] were associated with bullying in the study sample. Limitations: The present study is limited by its cross-sectional nature. Also, only two countries were surveyed from the European region Conclusions: Active commuting and attendance to physical education play a protective role for bullying, while physical activity does not. © 2020 Elsevier B.V.